Acupressure in the Management of Hyperemesis Gravidarum: A Systematic Analysis - Ariani, Novida (Jurnal EduHealth, 2024)
Pregnant women who experience more severe emesis gravidarum (nausea and vomiting) are known as hyperemesis gravidarum, this can affect the health of the mother and baby if not treated. To analyze and compile the latest scientific evidence to evaluate the benefits and techniques of acupressure as a method of managing emesis gravidarum, so that it does not develop into hyperemesis gravidarum. This research method is a systematic review with a systematic review based on PRISMA. Literature search based on research articles published in the last 10 years. Literature was obtained from a database of medium to high quality criteria using relevant keywords, namely "acupressure", "hyperemesis gravidarum", "nausea", "vomiting", "clinical study", "experimental study", then selected according to the inclusion and exclusion criteria of the study, appropriate research articles were continued in the PICOT table. Results: Ten studies that passed the inclusion criteria compared 5 different therapies where the most therapy used P6 acupressure and overall were considered to have a low risk of bias. The findings showed that acupressure can reduce the intensity of nausea and vomiting, reduce serum IL-6 levels, lower PUQE scores, better urine ketone results, reduce the frequency of antiemetic administration, and reduce the length of treatment. TherapyAcupressure has the potential to reduce symptoms of nausea and vomiting in pregnancy, especially to prevent the severity towards the diagnosis of Hyperemesis Gravidarum. However, further research with a validated scoring system, diagnostic criteria, clear outcome measures, and conducting larger studies is needed to confirm its effectiveness.